Victor Hugo's conversations with the spirit world a literary genius's hidden life - Hugo, Victor 1802-1885; Chambers, John (Destiny Books, 2008)
"First English translation of Victor Hugo's writings on his experiments in spiritualism"--Provided by publisher.
Rev. ed. of: Conversations with eternity. 1998.
Includes bibliographical references and index
Keywords: Table-moving (Spiritualism); Channeling (Spiritualism); Spiritualism; Channeling -- Parapsychologie; Tischrücken; Spiritismus